The tooth movement efficiency of different orthodontic thermoplastics for clear aligners: study protocol for a randomized controlled clinical trial - Chuangchuang Mu; Bingjing Sun; Zhicheng Gong; Yuanyuan Wei; Li Chen; Wei Zhang; Haimiao Wu; Bingjiao Zhao (Trials, 2023)
Abstract Introduction With regard to the esthetics and comfort of orthodontic treatment, the requirement for removable clear aligners (CAs) is increasing. Unlike conventional fixed orthodontic appliances, CAs were made of thermoplastic film by thermoforming on the personalized dental models. The construction of orthodontic thermoplastic is a critical factor for orthodontic tooth movement (OTM). Polyethylene terephthalate glycol-modified (PETG) and thermoplastic polyurethane (TPU) are the most commonly orthodontic thermoplastics; however, the evidence of the differences between different orthodontic thermoplastic are limited to vitro environment and the evidence in vivo environment is not available. Therefore, this trial aims to provide reliable evidence for orthodontists’ personalized treatment plans whether the two most commonly used orthodontic thermoplastics of PETG and TPU have differences in the efficiency of OTM. Methods and analysis This randomized controlled clinical study will recruit 44 orthodontic patients for orthodontic treatment. All the subjects will be randomized into two groups (PETG and TPU, n = 22 for each group). In the first stage (M0 to M1), clear aligners will be made of two orthodontic thermoplastics and move the maxillary first or second premolars 2 mm. In the second stage, patients will take the standard orthodontic treatments. The primary outcome will be the efficiency of clear aligners made of different materials on the digital models. The secondary outcome will be the efficiency of clear aligners made of different materials on the cone-beam computed tomography (CBCT). The efficiency will be calculated through the superimposition of the digital models and CBCT. Discussion The results from this trial will serve as evidence for orthodontists and manufacturers and clarify whether the difference in orthodontic thermoplastics significantly impacts the efficiency of OTM. Trial registration number ChiCTR2300070980. Registered on 27 April 2023. https://www.chictr.org.cn/showproj.html?proj=186253